1979
DOI: 10.1159/000117682
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Drugs in Chronic Schizophrenia

Abstract: The effect of dopaminergic-related and stimulatory drugs have been studied in chronic hebephrenic schizophrenics untreated with neuroleptic drugs. 6 patients received therapy of 2 g L-dopa + 200 mg carbodopa per day orally for 30 days, then placebo for 30 days. Following that 3 of the same patients received therapy of 2 g L-dopa + 200 mg carbodopa + 300 mg imipramine orally for 30 days, then placebo for 30 days. Following that the same 3 patients recieved 1 mg apomorphine s.c. for 15 days, then placebo for 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These studies have been reviewed by us elsewhere (Meltzer et al 1986) and by Christison and colleagues (1991). L-dopa and d- amphetamine act mainly to increase dopaminergic activity and may be of benefit, especially in patients with marked negative symptoms and few positive symptoms (Inanaga et al 1972; Gerlach and Luhdorf 1975; Brambilla et al 1979; Cesarec and Nyman 1985). Exacerbations of positive symptoms may occur in some patients (Yaryura-Tobias et al 1970; Angrist et al 1973; Calil et al 1977).…”
Section: Other Approaches To Treatment-resistant Schizophreniamentioning
confidence: 99%
“…These studies have been reviewed by us elsewhere (Meltzer et al 1986) and by Christison and colleagues (1991). L-dopa and d- amphetamine act mainly to increase dopaminergic activity and may be of benefit, especially in patients with marked negative symptoms and few positive symptoms (Inanaga et al 1972; Gerlach and Luhdorf 1975; Brambilla et al 1979; Cesarec and Nyman 1985). Exacerbations of positive symptoms may occur in some patients (Yaryura-Tobias et al 1970; Angrist et al 1973; Calil et al 1977).…”
Section: Other Approaches To Treatment-resistant Schizophreniamentioning
confidence: 99%
“…For example, a number of studies suggest that amphetamine may induce psychotic states that in some respects resemble schizophrenia (Connell, 1958;Ellinwood, 1967;Angrist and Gershon, 1970;Snyder, 1977) and worsen psychotic symptoms in patients with preexisting schizophrenia (Casey et al, 196 1;Chiarello and Cole, 1987, forreview). Paradoxically, however, there have been reports of efficacy of centrally active dopamine agonists in alleviating both positive symptoms (i.e., hallucinations, excitement, delusions) and, to a greater extent, so-called negative or defect symptoms (i.e., emotional blunting, anergy, anhedonia, amotivation, social withdrawal) in schizophrenia (Inanaga et al, 1972(Inanaga et al, , 1975Buchanan et al, 1975;Gerlach and Luhdorf, 1975;Ogura et al, 1976;Brambilla et al, 1979;Alpert and Rush, 1983;Kay et al, 1985-86;Opler et al, 1985). In the present study, patients with schizophrenia were treated simultaneously with (1) an antipsychotic (i.e., haloperidol) that has a relatively high affinity for blockade of subcortical D, receptors (Andersen et al, 1986;Tamminga and Gerlach, 1987), which are thought to be important in mediating positive psychotic symptoms, and (2) amphetamine, which in the presence of haloperidol would be expected to stimulate preferentially D, receptors.…”
Section: Amphetamine and Schizophreniamentioning
confidence: 99%
“…Over a 10-month period, the general estimated prevalence of exacerbation in schizophrenia is 16% in APD-treated individuals but 56% in patients who are not taking APDs (Gilbert et al 1995). The majority (84%) of patients in the current review who received l-dopa without concomitant APDs did so for less than 4 weeks Alpert et al 1978;Brambilla et al 1979;Beramendi et al 1980;Davidson et al 1987). Furthermore, insofar as l-dopa increases verbal communicativeness (Yaryura-Tobias et al 1971), rating scales that depend on self-reporting of symptoms may overestimate the emergence of psychotic symptoms in the previously withdrawn patient.…”
Section: Discussionmentioning
confidence: 74%
“…2); all three studies in which over 20% of patients worsened (Yaryura-Tobias et al 1970a, 1970bCalil et al 1977) had very small patient samples (n 4). A total of 64 patients in five studies received l-dopa without concomitant APDs; 38% of the latter showed definite worsening Alpert et al 1978;Brambilla et al 1979;Beramendi et al 1980, Davidson et al 1987. Inanaga et al (1975a) 0.2722 0.1670 Asano et al (1973) 3.6129 0.0000 Fleming et al (1970) 1.6000 0.0774 Gerlach and Luhdorf (1975) 0.8275 0.0366 Overall 0.7116 0.0000…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation